THE ROLE OF EDUCATION IN THE FAMILY - Toshpulatov Ibrohim Ikromjonovich; Xaminjonov Azamat Ahmadali o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article discusses the role of parents in the education of children in the family, and it is emphasized that the issue of education is relevant and does not lose its importance in any era and in any society. Also, the significance of the views of scholars and scientists of our nation on child upbringing and education in the family today has been studied.